Post-modernist motives in prose Aygul Kemelbayeva (Eurasian Journal of Philology Science and Education, 2015)
Article considers post-modernist motives in prose Aygul Kemelbayeva. In article examines the stories of the writer «Тobilgicay», «Agash uy ». In the stories «Ағаш үй» (Wooden house) and «Тобылғысай» (Ravine with meadowsweet) written by A.Kemelbayeva an ideology of the hero constitutes a system of artistic vision, the analysis of these works proved them to be based on postmodernism flow. Main oneiric elements (imagination, dreams, thoughts), which express the first sketches of the postmodern flow, became distinctive features of these works. Furthermore, in her stories A.Kemelbayeva pays close attention to moments such as a state coercion, dreaming and disturbance of consciousness, these works also contain clear expression of postmodernist features.
Keywords: prose; direction; appearance; modernism; post-modernism